2007
DOI: 10.1111/j.1572-0241.2007.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Study to Assess Efficacy and Safety of 0.5 mg and 1 mg Alosetron in Women With Severe Diarrhea-predominant IBS

Abstract: Alosetron 0.5 mg and 1 mg once daily as well as 1 mg twice daily are effective in providing global improvement in IBS symptoms, adequate relief of IBS pain and discomfort, and improvement in bowel symptoms in women with severe d-IBS. Lower dosing regimens resulted in a decreased constipation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 33 publications
1
107
0
1
Order By: Relevance
“…For years, tricyclic antidepressants have been used to help target pain and take advantage of the side effect of constipation to help address stool consistency [12] . Alosetron, a 5HT3 antagonist, was approved for women with severe IBS-D because serotonin has been shown to affect motility and pain, but the side effect profile has limited use of the product [13,14] . Rifaximin, an oral antibiotic, has demonstrated some potential for some IBS-D patients [15,16] .…”
Section: Case Presentation #1mentioning
confidence: 99%
“…For years, tricyclic antidepressants have been used to help target pain and take advantage of the side effect of constipation to help address stool consistency [12] . Alosetron, a 5HT3 antagonist, was approved for women with severe IBS-D because serotonin has been shown to affect motility and pain, but the side effect profile has limited use of the product [13,14] . Rifaximin, an oral antibiotic, has demonstrated some potential for some IBS-D patients [15,16] .…”
Section: Case Presentation #1mentioning
confidence: 99%
“…Following substantial public pressure, it was re-introduced into the U.S. market in 2002 under a restricted prescribing program and further post-marketing studies are currently underway. In a recent placebo-controlled study, Krause and colleagues examined the safety and efficacy of alosetron at varying doses, and found that one of 250 patients developed self-limited ischemic colitis (0.5 mg daily) [47] . In a systematic review of post-marketing surveillance data, Chang and colleagues estimated the rate of ischemic colitis to be 1.1 per 1 000 patients.…”
Section: -Ht3 Antagonistsmentioning
confidence: 99%
“…Compared with placebo, alosetron demonstrated effectiveness in decreasing fecal urgency and improving stool consistency and frequency in women with IBS-D (Figures 1 and 2) [Krause et al 2007;Lembo et al 2004Lembo et al , 2001. Alosetron has been shown to significantly improve IBS-related abdominal pain and discomfort in randomized, double-blind clinical trials (Figure 3) [Krause et al 2007;Camilleri et al 2001Camilleri et al , 2000. [Hahn et al 1997].…”
Section: Efficacy Of Alosetronmentioning
confidence: 99%
“…[Ameen et al 2008;Chang et al 2006] and no confirmed serious outcomes have been reported (e.g. surgeries, transfusions, deaths) to result from these events [Ameen et al 2008;Krause et al 2007;Chang et al 2006]. The risk of developing IC and the pathologic mechanism by which alosetron might cause this adverse event remains unclear [Camilleri, 2007].…”
Section: Postmarketing Surveillance After Reintroduction (November 20mentioning
confidence: 99%